Identifying Climate Change Adaptation Efforts in the Batutegi Forest Management Unit, Indonesia - Wulandari, Christine (Forest and Society, 2021)
The Batutegi Forest Management Unit (FMU) in Lampung Province, Indonesia is beginning to observe the consequences of climate change. Meanwhile, communities in Batutegi are also suggesting that effects of climate change are becoming more prominent in their region. Indicators include rising air temperature and the increasing regularity of extreme weather changes. Studies show that land cover has decreased by up to 95% in the region. As these trends intensify, predictions note that the Batutegi reservoir and the productivity of the surrounding protected forests will be affected. This research examines FMU efforts to adapt to vulnerabilities from environmental and climate change. The broader objective of this research is to determine the appropriate climate change adaptation efforts, specifically regarding the management of sustainable forest protection. The method is conducted through regression analysis to identify significant variables and applies the Analytic Hierarchy Process (AHP) to identify priorities for planned interventions for climate change adaptation by the FMU. Based on regression results there were four significant variables, i.e. appropriate agroforestry initiatives, non-timber forest products, community institutional support, and local policy engagement. This research also considers various kinds of technologies of adaptation applied by local communities. Examining community efforts also presents possibilities for improving FMU institutional planning that is locally responsive. This is done primarily through agroforestry techniques and other community conservation practices. Based on the result of the AHP analysis, the findings highlight various programs related to agroforestry technologies as the top priority. Thereafter, priorities point to institutional development policies. Together, these priorities can form the basic considerations for developing climate change adaptation policies in Batutegi. These policies can be applied with, and by communities in managing forests through agroforestry, beginning with support for high quality seed procurement that also supports all phases of cultivation and supply chain through final product marketing. As a result, forest productivity and support for local income can form a robust approach for fulfilling community needs despite the effects of environmental and climate change in Batutegi.